PENGARUH PUPUK KASCING DAN NPK MUTIARA 16:16:16 TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN SELEDRI (Apium graviolens L.) - Yurnie Sari Alphiani; Zulkifli; Sulhaswardi (UIR Press, 2018)
ABSTRACT The purpose of this study is to determine the effect of interaction and the main influence of vermicompost and NPK Pearl 16:16:16 on the growth and yield of celery plants. This research was carried out for four months, from August to November 2018. This research used a factorial completely randomized design (RAL) consisting of two factors, where the first factor was vermicompost fertilizer (K) consisting of 4 levels, namely 0, 60, 80, 100 g / polybag and the second factor is NPK Pearl 16:16:16 (N) fertilizer consisting of 4 levels, 0, 0.8, 1.6, 2.4 g/polybag. The observation parameters in this study were plant height (cm), relative growth rate (g), root volume (cm3), number of tillers, number of midribs, wet weight of crop (g), and age of harvest (days). The last observation data were statistically analyzed and continued with a BNJ follow-up test at the 5% level. The results showed that the interaction between vermicompost and NPK Pearl 16:16:16 fertilizer significantly affected plant height from week two to week seven, the relative growth rate in the first week, root volume, number of tillers, number of fronds and wet weight per plant. The best treatment is K3N3 (K3 vermicompost fertilizer = 100 g /polybag and NPK Pearl 16:16:16 N3 = 2,4 g/polybag), but it has no significant effect on the age of harvest and the main effect of vermicompost and NPK Pearl 16:16: 16 significantly affected plant height, relative growth rate, root volume, number of tillers, number of midribs and wet weight of the crop, with the best treatment being K3 (vermicompost fertilizer 100 g/polybag) and N3 (NPK Pearl 16:16:16 2,4 g/polybag). Keywords: Celery, Vermicompost, NPK pearl 16:16:16